Screening of Group B Streptococcus in pregnancy: A systematic review for the laboratory detection - Arsenijević Valentina Arsić; Gerginić Vladimir; Miličić Biljana; Jurišić Aleksandar; Petričević Ljubomir (Open Medicine)
Group B Streptococcus (GBS) is important since almost 1/3 of pregnant women are colonized with GBS, and as much as 50% passes to the newborns, sometimes resulting in severe neonatal infections; that is why there are mandatory guidelines for antepartum screening for GBS vaginal/rectal colonization. Also, bacteria other than GBS and yeasts may affect newborns; therefore, an increase in the current knowledge and improving the guidelines related to the prediction and prevention of neonatal early-onset infections are needed.